Effect of Cement Stabilization on Shear Strength Parameters of Soft Soils on Agricultural Road - Cheng Liu, Aldington Jian; Abu Talib, Zaihasra; Yian Bong, Jia; Ling, Felix N. L.; Yunusa, Gambo Haruna (International Journal of Sustainable Construction Engineering and Technology, 2024)
Agricultural roads play a crucial role in facilitating transportation in agricultural regions, including horticulture, smallholder farms and plantations. However, the agricultural roads in Sungai Balang, Muar face challenges due to the poor condition of the soft soil. Soft soil is characterized by low shear strength, high compressibility and large settlements, making it unsuitable for efficient road infrastructure. To address these issues, cement stabilization has been proposed in this study as a potential solution to improve the soft soil on agricultural roads in the paddy field area of Sungai Balang. The objectives of this study are to identify the classification of the soft soil on agricultural roads in Sungai Balang through grain size analysis, moisture content test, specific gravity test, Atterberg limit test and standard proctor compaction test and to determine the effectiveness of cement stabilization through direct shear test. The direct shear test was carried out to evaluate the shear strength parameters of the soil on the agricultural roads before and after the addition of different percentages of cement (5%, 10% and 15% by dry weight of the soft soil). The results of soil classification showed that the soft soil on agricultural roads in Sungai Balang was classified as MH, which was silty soil with high plasticity. Besides, the results of direct shear test indicated that the 15% cement specimen achieved the optimum percentages compared to the others. The friction angle of the 15% cement specimen had increased from 28o to 43o and the cohesion had increased from 28.33 kPa to 85.00 kPa compared to the untreated soil samples. By studying the effects of different percentages of cement on soil settlements, the research provides insights into the performance and suitability of cement stabilization in enhancing the stability and strength of soft soils on agricultural roads.